Relationship between the siring capacity of beef bulls and their behaviour in multi-sire breeding groups measured by remote monitoring technologies - Vinicius A. Camargo; Edmond A. Pajor; Mathieu Pruvot; Sayeh Bayat; James C. Cross; Jennifer M. Pearson (Theriogenology, 2026)

Spatial distribution of persistent components of particulate matter near a hazardous waste thermal treatment facility - Chuqi Guo; Oluwafeyikemi Ogunmusi; Martine E. Mathieu-Campbell; Myron Lard; Thomas Blanchard; Lavrent Khachatryan; Brenda Vallee; Wilma Subra; Stephania A. Cormier; Slawo Lomnicki; Jennifer Richmond-Bryant (Environmental Pollution, 2026)

Persistent chemicals in particulate matter (PM) near a hazardous waste thermal treatment facility - Chuqi Guo; Martine E. Mathieu-Campbell; Thomas Blanchard; Lavrent Khachatryan; Md Abdullah Al-Mamun; Qingzhao Yu; Myron Lard; Oluwafeyikemi Ogunmusi; Brenda Vallee; Wilma Subra; Iriel Edwards; David Malone; et al. (Atmospheric Pollution Research, 2026)

The role of broadleaved hedgerows for biodiversity conservation in pine plantation landscape - Nattan Plat; Eric Allan; Severin Jouveau; Olivier Bonnard; Jean-Baptiste Rivoal; Jennifer Dudit; Tom Barlier; Yohan Charbonnier; Mathieu Sannier; Irene Garcia-Celada; Inge van Halder; Hervé Jactel (Biodiversity and Conservation, 2026)

Impact of phytoplankton, CDOM, and suspended sediments on the vertical attenuation of light, changing heat content and circulation on a continental shelf: A modelling study of the Great Barrier Reef - Anna Maggiorano; Mark Baird; Clothilde Langlais; Mathieu Mongin; Jennifer Skerratt (Ocean Modelling, 2025)

A Latitudinal Cline in the Taxonomic Structure of Eelgrass Epifaunal Communities is Associated With Plant Genetic Diversity - Collin P. Gross; J. Emmett Duffy; Kevin A. Hovel; Pamela L. Reynolds; Christoffer Boström; Katharyn E. Boyer; Mathieu Cusson; Johan Eklöf; Aschwin H. Engelen; Britas Klemens Eriksson; F. Joel Fodrie; John N. Griffin; et al. (Global Ecology and Biogeography, 2024)
Aim Biogenic structural complexity increases mobile animal richness and abundance at local, regional and global scales, yet animal taxa vary in their response to complexity. When these taxa also vary functionally, habitat structures favouring certain taxa may have consequences for ecosystem function. We characterised global patterns of epifaunal invertebrates in eelgrass ( Zostera marina ) beds that varied in structural and genetic composition. Location North America, Europe and Asia. Time Period 2014. Major Taxa Studied Peracarid crustaceans and gastropod molluscs. Methods We sampled epifaunal invertebrate communities in 49 eelgrass beds across 37° latitude in two ocean basins concurrently with measurements of eelgrass genetic diversity, structural complexity and other abiotic and biotic environmental variables. We examined how species richness, abundance and community composition varied with latitude and environmental predictors using a random forest approach. We also examined how functional trait composition varied along with community structure. Results Total species richness decreased with latitude, but this was accompanied by a taxonomic shift in dominance from peracarid crustaceans to gastropods, which exhibited different sets of functional traits. Greater eelgrass genetic diversity was strongly correlated with both richness and abundance of peracarids, but less so for gastropods. Main Conclusions Our results add to a growing body of literature that suggests genetic variation in plant traits influences their associated faunal assemblages via habitat structure. Because peracarids and gastropods exhibited distinct functional traits, our results suggest a tentative indirect link between broad‐scale variation in plant genetic diversity and ecosystem function.

Transrectal ultrasonographic assessment of the fetal proximal phalanx: A new tool to assess fetal age and bone development in horses - Catherine Renaudin; Fiona Wensley; Jessica Morgan; Jennifer Cassano; Mathieu Spriet (Theriogenology, 2024)

Shade tree functional traits drive critical ecosystem services in cocoa agroforestry systems - Shalom D. Addo-Danso; Richard Asare; Abigail Tettey; Jennifer E. Schmidt; Marie Sauvadet; Mathieu Coulis; Nelly Belliard; Marney E. Isaac (Agriculture, Ecosystems & Environment, 2024)

Tectono-sedimentary evolution of the Suriname margin in the cretaceous: A sequence-stratigraphic framework - V. Delhaye-Prat; Julien Bourget; Gwladys Gaillot; Jérémie Gaillot; François Sapin; Charlotte Fillon; Jing Ye; Tim Wright; Anne-Claire Chaboureau; Nicoletta Buratti; Benoit Magnier; Andrei Belopolsky; et al. (Earth-Science Reviews, 2024)

Persistent headaches one year after bacterial meningitis: prevalence, determinants and impact on quality of life - Rémi Nguyen Van; Sarah Tubiana; Thomas De Broucker; Joseph Cédric; Carine Roy; Marie-Caroline Meyohas; Thierry Prazuck; Catherine Chirouze; Bruno Hoen; Xavier Duval; Matthieu Revest; Bruno Mourvillier; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2023)

Derivation of Naïve Human Embryonic Stem Cells Using a CHK1 Inhibitor - Carol B. Ware; Erica C. Jonlin; Donovan J. Anderson; Christopher Cavanaugh; Jennifer Hesson; Sonia Sidhu; Savannah Cook; Guillermo Villagomez-Olea; Marshall S. Horwitz; Yuliang Wang; Julie Mathieu (Stem Cell Reviews and Reports, 2023)
Embryonic development is a continuum in vivo . Transcriptional analysis can separate established human embryonic stem cells (hESC) into at least four distinct developmental pluripotent stages, two naïve and two primed, early and late relative to the intact epiblast. In this study we primarily show that exposure of frozen human blastocysts to an inhibitor of checkpoint kinase 1 (CHK1) upon thaw greatly enhances establishment of karyotypically normal late naïve hESC cultures. These late naïve cells are plastic and can be toggled back to early naïve and forward to early primed pluripotent stages. The early primed cells are transcriptionally equivalent to the post inner cell mass intermediate (PICMI) stage seen one day following transfer of human blastocysts into in vitro culture and are stable at an earlier stage than conventional primed hESC. Graphical Abstract

Characteristics of upward-connecting-leader current leading to attachment in downward negative cloud-to-ground lightning strokes - Amitabh Nag; Kenneth L. Cummins; Mathieu N. Plaisir; Robert G. Brown; Jennifer G. Wilson; David E. Crawford; R. Carl Noggle; Hamid K. Rassoul (Atmospheric Research, 2023)

Development of the Healthy Eating Index-Toddlers-2020 - TusaRebecca E. Pannucci; Jennifer L. Lerman; Kirsten A. Herrick; Marissa M. Shams-White; Meghan Zimmer; Kevin Meyers Mathieu; Eve E. Stoody; Jill Reedy (Journal of the Academy of Nutrition and Dietetics, 2023)

Continuity, Considerations, and Future Directions for the Healthy Eating Index-Toddlers-2020 - Kirsten A. Herrick; Jennifer L. Lerman; TusaRebecca E. Pannucci; Meghan Zimmer; Marissa M. Shams-White; Kevin Meyers Mathieu; Eve E. Stoody; Jill Reedy (Journal of the Academy of Nutrition and Dietetics, 2023)

Evaluation of the Healthy Eating Index-Toddlers-2020 - Jennifer L. Lerman; Kirsten A. Herrick; TusaRebecca E. Pannucci; Marissa M. Shams-White; Lisa L. Kahle; Meghan Zimmer; Kevin Meyers Mathieu; Eve E. Stoody; Jill Reedy (Journal of the Academy of Nutrition and Dietetics, 2023)

Healthy Eating Index-2020: Review and Update Process to Reflect the Dietary Guidelines for Americans, 2020-2025 - Marissa M. Shams-White; TusaRebecca E. Pannucci; Jennifer L. Lerman; Kirsten A. Herrick; Meghan Zimmer; Kevin Meyers Mathieu; Eve E. Stoody; Jill Reedy (Journal of the Academy of Nutrition and Dietetics, 2023)

Dispersal of the pesticide diuron in the Great Barrier Reef - Jennifer Skerratt; Mark E. Baird; Mathieu Mongin; Robin Ellis; Rachael A. Smith; Melanie Shaw; Andy D.L. Steven (Science of The Total Environment, 2023)

When bioregionalisation emphasises the presence of vulnerable marine ecosystem indicator species in Nephrops fishing grounds: Evidence in the Bay of Biscay/Irish Sea continuum - Anna Le Joncour; Maud Mouchet; Boris Leroy; Jennifer Doyle; Mathieu Lundy; Marianne Robert; Dorothée Kopp (Progress in Oceanography, 2023)

Fetal ultrasonography of the distal limb: a new tool to assess equine fetal age and bone development - Catherine D Renaudin; Fiona M Wensley; Jessica M Morgan; Jennifer M Cassano; Mathieu Spriet (Journal of Equine Veterinary Science, 2023)

Consensus Recommendations for Clinical Outcome Assessments and Registry Development in Ataxias: Ataxia Global Initiative (AGI) Working Group Expert Guidance - Thomas Klockgether; Matthis Synofzik; Saud Alhusaini; Mathieu Anheim; Irina Antonijevic; Tee Ashizawa; Luis Bataller; Mélanie Berard; Enrico Bertini; Sylvia Boesch; Pedro Braga-Neto; Emanuel Cassou; et al. (The Cerebellum, 2023)
To accelerate and facilitate clinical trials, the Ataxia Global Initiative (AGI) was established as a worldwide research platform for trial readiness in ataxias. One of AGI’s major goals is the harmonization and standardization of outcome assessments. Clinical outcome assessments (COAs) that describe or reflect how a patient feels or functions are indispensable for clinical trials, but similarly important for observational studies and in routine patient care. The AGI working group on COAs has defined a set of data including a graded catalog of COAs that are recommended as a standard for future assessment and sharing of clinical data and joint clinical studies. Two datasets were defined: a mandatory dataset (minimal dataset) that can ideally be obtained during a routine clinical consultation and a more demanding extended dataset that is useful for research purposes. In the future, the currently most widely used clinician-reported outcome measure (ClinRO) in ataxia, the scale for the assessment and rating of ataxia (SARA), should be developed into a generally accepted instrument that can be used in upcoming clinical trials. Furthermore, there is an urgent need (i) to obtain more data on ataxia-specific, patient-reported outcome measures (PROs), (ii) to demonstrate and optimize sensitivity to change of many COAs, and (iii) to establish methods and evidence of anchoring change in COAs in patient meaningfulness, e.g., by determining patient-derived minimally meaningful thresholds of change.

Sex-specific relationships between obesity, physical activity, and gray and white matter volume in cognitively unimpaired older adults - Brittany Intzandt; Safa Sanami; Julia Huck; Anne Labonté; Alexa Pichet Binette; Axel Mathieu; Cynthia Picard; Doris Dea; Claudio Cuello; Alan Evans; Christine Tardif; Gerhard Mulhaup; et al. (GeroScience, 2023)

Advancing fishery-independent stock assessments for the Norway lobster (Nephrops norvegicus) with new monitoring technologies - Jacopo Aguzzi; Damianos Chatzievangelou; Nathan J. Robinson; Nixon Bahamon; Alan Berry; Marc Carreras; Joan Batista Company; Corrado Costa; Joaquin del Rio Fernandez; Ahmad Falahzadeh; Spyros Fifas; Sascha Flögel; et al. (Frontiers in Marine Science, 2022)
The Norway lobster, Nephrops norvegicus , supports a key European fishery. Stock assessments for this species are mostly based on trawling and UnderWater TeleVision (UWTV) surveys. However, N. norvegicus are burrowing organisms and these survey methods are unable to sample or observe individuals in their burrows. To account for this, UWTV surveys generally assume that “1 burrow system = 1 animal”, due to the territorial behavior of N. norvegicus . Nevertheless, this assumption still requires in-situ validation. Here, we outline how to improve the accuracy of current stock assessments for N. norvegicus with novel ecological monitoring technologies, including: robotic fixed and mobile camera-platforms, telemetry, environmental DNA (eDNA), and Artificial Intelligence (AI). First, we outline the present status and threat for overexploitation in N. norvegicus stocks. Then, we discuss how the burrowing behavior of N. norvegicus biases current stock assessment methods. We propose that state-of-the-art stationary and mobile robotic platforms endowed with innovative sensors and complemented with AI tools could be used to count both animals and burrows systems in-situ , as well as to provide key insights into burrowing behavior. Next, we illustrate how multiparametric monitoring can be incorporated into assessments of physiology and burrowing behavior. Finally, we develop a flowchart for the appropriate treatment of multiparametric biological and environmental data required to improve current stock assessment methods.

Rapid Treatment with Intramuscular Magnesium Sulfate During Cardiopulmonary Resuscitation Does Not Provide Neuroprotection Following Cardiac Arrest - Rui Zhang; Timothy D. Bryson; Garrett M. Fogo; Jinhui Liao; Sarita Raghunayakula; Jennifer Mathieu; Joseph M. Wider; Xiaodan Ren; Kathleen J. Maheras; Katlynn J. Emaus; Erin Gruley; Yuguo Chen; et al. (Molecular Neurobiology, 2022)

Joint effects of patch edges and habitat degradation on faunal predation risk in a widespread marine foundation species - Kevin A. Hovel; J. Emmett Duffy; John J. Stachowicz; Pamela Reynolds; Christoffer Boström; Katharyn E. Boyer; Stéphanie Cimon; Mathieu Cusson; Fredrick Joel Fodrie; Karine Gagnon; Clara M. Hereu; Masakazu Hori; et al. (Ecology, 2021)
Human activities degrade and fragment coastal marine habitats, reducing their structural complexity and making habitat edges a prevalent seascape feature. Though habitat edges frequently are implicated in reduced faunal survival and biodiversity, results of experiments on edge effects have been inconsistent, calling for a mechanistic approach to the study of edges that explicitly includes indirect and interactive effects of habitat alteration at multiple scales across biogeographic gradients. We used an experimental network spanning 17 eelgrass ( Zostera marina ) sites across the Atlantic and Pacific oceans and the Mediterranean Sea to determine (1) if eelgrass edges consistently increase faunal predation risk, (2) whether edge effects on predation risk are altered by habitat degradation (shoot thinning), and (3) whether variation in the strength of edge effects among sites can be explained by biogeographical variability in covarying eelgrass habitat features. Contrary to expectations, at most sites, predation risk for tethered crustaceans (crabs or shrimps) was lower along patch edges than in patch interiors, regardless of the extent of habitat degradation. However, the extent to which edges reduced predation risk, compared to the patch interior, was correlated with the extent to which edges supported higher eelgrass structural complexity and prey biomass compared to patch interiors. This suggests an indirect component to edge effects in which the impact of edge proximity on predation risk is mediated by the effect of edges on other key biotic factors. Our results suggest that studies on edge effects should consider structural characteristics of patch edges, which may vary geographically, and multiple ways that humans degrade habitats.

Latitudinal variation in plant defence against herbivory in a marine foundation species does not follow a linear pattern: The importance of resource availability - Gema Hernán; María J. Ortega; Jeremy Henderson; Josep Alós; Katharyn Boyer; Stephanie Cimon; Vincent Combes; Mathieu Cusson; Clara M. Hereu; Margot Hessing‐Lewis; Kevin Hovel; Pablo Jorgensen; et al. (Global Ecology and Biogeography, 2021)
Aim Studies on latitudinal patterns in plant defence have traditionally overlooked the potential effect that resource availability may have in shaping plant defence. Likewise, latitudinal patterns of tolerance traits have rarely been studied, yet they can be a critical component of plant defence. Therefore, the aim of our study was to examine latitudinal variation in the production of tolerance and resistance traits against herbivory along a latitudinal range and a natural gradient of resource availability from upwelling conditions. Location North America (Canada, USA, Mexico). Time period Summer months of 2015. Major taxa used The seagrass Zostera marina . Methods We conducted experiments simulating macroherbivore (e.g., bird, fish) damage on the seagrass Z. marina at 10 sites across the Eastern Pacific coast (Canada–Mexico) and Quebec and analysed several traits related to resistance and tolerance strategies against herbivory. In addition, we examined the effects of potential seagrass changes in defence strategies by performing a series of feeding experiments with mesoherbivores in a subset of sites. Results We found that eelgrass resistance defences did not follow a linear latitudinal pattern but rather followed a bell‐shaped curve which correlated with bottom‐up control. In sites with higher nutrient availability, plants allocated resources to tolerance strategies and had lower resistance traits. Furthermore, seagrasses did not respond linearly to increased herbivory pressure; while they tolerated moderate levels of herbivory, they underwent a significant reduction in tolerance and resistance under high herbivory levels, which also made them more susceptible to consumers in feeding experiments. Main conclusions Our results highlight the importance that nutrient availability has in shaping latitudinal patterns of plant defence against herbivory and show how these defences may not respond linearly to increased herbivory pressure in seagrasses.

Dendritic sodium spikes endow neurons with inverse firing rate response to correlated synaptic activity - Tomasz Górski; Romain Veltz; Mathieu Galtier; Hélissande Fragnaud; Jennifer S. Goldman; Bartosz Teleńczuk; Alain Destexhe (Journal of Computational Neuroscience, 2018)

Latitude, temperature, and habitat complexity predict predation pressure in eelgrass beds across the Northern Hemisphere - Pamela L. Reynolds; John J. Stachowicz; Kevin Hovel; Christoffer Boström; Katharyn Boyer; Mathieu Cusson; Johan S. Eklöf; Friederike G. Engel; Aschwin H. Engelen; Britas Klemens Eriksson; F. Joel Fodrie; John N. Griffin; et al. (Ecology, 2018)
Latitudinal gradients in species interactions are widely cited as potential causes or consequences of global patterns of biodiversity. However, mechanistic studies documenting changes in interactions across broad geographic ranges are limited. We surveyed predation intensity on common prey (live amphipods and gastropods) in communities of eelgrass ( Zostera marina ) at 48 sites across its Northern Hemisphere range, encompassing over 37° of latitude and four continental coastlines. Predation on amphipods declined with latitude on all coasts but declined more strongly along western ocean margins where temperature gradients are steeper. Whereas in situ water temperature at the time of the experiments was uncorrelated with predation, mean annual temperature strongly positively predicted predation, suggesting a more complex mechanism than simply increased metabolic activity at the time of predation. This large‐scale biogeographic pattern was modified by local habitat characteristics; predation declined with higher shoot density both among and within sites. Predation rates on gastropods, by contrast, were uniformly low and varied little among sites. The high replication and geographic extent of our study not only provides additional evidence to support biogeographic variation in predation intensity, but also insight into the mechanisms that relate temperature and biogeographic gradients in species interactions.

MicroRNAs as key regulators of xenobiotic biotransformation and drug response - Jennifer Bolleyn; Joery De Kock; Robim Marcelino Rodrigues; Mathieu Vinken; Vera Rogiers; Tamara Vanhaecke (Archives of Toxicology, 2015)

Biodiversity mediates top–down control in eelgrass ecosystems: a global comparative‐experimental approach - J. Emmett Duffy; Pamela L. Reynolds; Christoffer Boström; James A. Coyer; Mathieu Cusson; Serena Donadi; James G. Douglass; Johan S. Eklöf; Aschwin H. Engelen; Britas Klemens Eriksson; Stein Fredriksen; Lars Gamfeldt; et al. (Ecology Letters, 2015)
Nutrient pollution and reduced grazing each can stimulate algal blooms as shown by numerous experiments. But because experiments rarely incorporate natural variation in environmental factors and biodiversity, conditions determining the relative strength of bottom–up and top–down forcing remain unresolved. We factorially added nutrients and reduced grazing at 15 sites across the range of the marine foundation species eelgrass ( Zostera marina ) to quantify how top–down and bottom–up control interact with natural gradients in biodiversity and environmental forcing. Experiments confirmed modest top–down control of algae, whereas fertilisation had no general effect. Unexpectedly, grazer and algal biomass were better predicted by cross‐site variation in grazer and eelgrass diversity than by global environmental gradients. Moreover, these large‐scale patterns corresponded strikingly with prior small‐scale experiments. Our results link global and local evidence that biodiversity and top–down control strongly influence functioning of threatened seagrass ecosystems, and suggest that biodiversity is comparably important to global change stressors.

Bcl10 is an essential regulator for A20 gene expression - Wu Xu; Liquan Xue; Yi Sun; Aline Henry; Jennifer M. Battle; Mathieu Micault; Stephan W. Morris (Journal of Physiology and Biochemistry, 2013)

Recent advances in 2D and 3D in vitro systems using primary hepatocytes, alternative hepatocyte sources and non-parenchymal liver cells and their use in investigating mechanisms of hepatotoxicity, cell signaling and ADME - Patricio Godoy; Nicola J. Hewitt; Ute Albrecht; Melvin E. Andersen; Nariman Ansari; Sudin Bhattacharya; Johannes Georg Bode; Jennifer Bolleyn; Christoph Borner; Jan Böttger; Albert Braeuning; Robert A. Budinsky; et al. (Archives of Toxicology, 2013)

Induction of insolubility by herpes simplex virus VP22 precludes intercellular trafficking of N-terminal Apoptin-VP22 fusion proteins - Saskia A. Rutjes; Piter J. Bosma; Jennifer L. Rohn; Mathieu H. M. Noteborn; John G. Wesseling (Journal of Molecular Medicine, 2003)